Localized basis approach to many-body effects and dielectric response - Hogan, Conor David (Trinity College (Dublin, Ireland). School of Physics, 2001)
This thesis is a study of the optical and dielectric properties of semiconductors and insulators, and of the way in which these properties provide insight into the microscopic response of the interacting system. The central component of this work is the wavevector and frequency dependent dielectric function, e(q,w), which provides the link between the observed experimental phenomena of absorption and reflection on one side, and the quantum mechanical electronic structure that determines the fundamental nature of the response mechanisms on the other.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin